The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1086/308113
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Modeling of the Solar Transition Region. II. Identification of New Classes of Solutions of Coronal Loop Models

Abstract: In the present work we undertake a study of the quasi-static loop model and the observational consequences of the various solutions found. We obtain the most general solutions consistent with certain initial conditions. Great care is exercised in choosing these conditions to be physically plausible (motivated by observations). We show that the assumptions of previous quasi-static loop models, such as the models of Rosner, Tucker, & Vaiana (RTV) and Veseckey, Antiochos, & Underwood, (VAU) are not necessarily va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 60 publications
5
26
1
Order By: Relevance
“…The basic input of the theory is the reasonable assumption that the coronal structures are created from the evolution and re-organization of a relatively cold plasma flow [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] emerging from the sub-coronal region (between the solar surface and the visible corona) and interacting with the ambient magnetic field anchored inside the solar surface. During the process of trapping and accumulation, a part of the kinetic energy of the flow is converted to heat by viscous dissipation and the coronal structure is born hot and bright.…”
Section: Introductionmentioning
confidence: 99%
“…The basic input of the theory is the reasonable assumption that the coronal structures are created from the evolution and re-organization of a relatively cold plasma flow [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] emerging from the sub-coronal region (between the solar surface and the visible corona) and interacting with the ambient magnetic field anchored inside the solar surface. During the process of trapping and accumulation, a part of the kinetic energy of the flow is converted to heat by viscous dissipation and the coronal structure is born hot and bright.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results have also shown that simple scaling laws may not be universally applicable, not holding for some loop classes such as cool transition region loops (Oluseyi et al 1999a(Oluseyi et al , 1999b or Ñaring loops (Garcia 1998), while and Aschwanden, Nightengale, & Alexander (2000a) have also highlighted inconsistencies associated with scaling law relationships. The EUV instruments on board SOHO and particularly T RACE have further added to our ability to measure coronal plasma properties in addition to studying the morphology of solar features, a fact that is clearly highlighted in Aschwanden et al (1999Aschwanden et al ( , 2000aAschwanden et al ( , 2000b.…”
Section: Introductionmentioning
confidence: 99%
“…Two aspects of this event's evolution hint at TCR as its formation mechanism. First, these two individual loop structures, both in close proximity to one another, likely share a footpoint rooted in the center of a supergranulation cell (Oluseyi et al 1999a(Oluseyi et al , 1999b. The convergence of these footpoints leads to propagating brightenings that fill these two loop structures until the full non-potential structure is formed.…”
Section: B August 05mentioning
confidence: 99%
“…First, it has been shown that the QS network at EUV temperatures is dominated by crowded loop structures with one footpoint rooted in the network lanes (Feldman et al 1999;Oluseyi et al 1999aOluseyi et al , 1999bWarren & Winebarger 2000). The close proximity of such loops and the sharing of footpoints elevate such structures as prime candidates for the TCR process.…”
Section: General Commentsmentioning
confidence: 99%
See 1 more Smart Citation